THE FAMILY'S INFLUENCE IN SOCIETY - Abdurashidova is the daughter of Mubarak Abdurashid (American Journals, 2023)
This article provides information about the main directions of the family's delicate role in society, emotional support, care and responsibilities.
Keywords: The role of the family in society, the family is the primary socializer, Emotional support, Families are kindness.